Mental health and cognitive outcomes associated with early childhood violence exposure: a focus on children in low-middle income countries (LMICs) - Tsunga, Lucinda Panashe (Department of Paediatrics and Child Health, 2025)
Knowledge about the exposure patterns of violence among preschoolers in low- and middle income countries (LMICs) is still limited. Furthermore, little is known about the associations of violence exposure with mental health or cognitive functioning in this age group. This is important, given that children in LMICs experience a high burden of violence and therefore alongside policies to reduce violence exposure, understanding the impacts of violence can guide early interventions to mitigate its adverse effects. In my thesis, I conducted two systematic reviews synthesizing the evidence on the mental health and cognitive outcomes associated with violence exposure in children in LMICs and identifying key gaps in the current literature. I further, directly investigated the lifetime violence exposure patterns of preschoolers in the Drakenstein Child Health Study (DCHS) in South Africa and subsequently investigated associations between lifetime childhood violence exposure at 4.5 years and mental health and cognitive outcomes at 5 years in this cohort. Approximately 70% of the 17 reviewed studies from 20 LMICs found associations between violence exposure and poor cognitive outcomes in childhood, while all 58 reviewed studies from 26 LMICs found associations between violence exposure and mental health problems in childhood. In my own study in the DCHS, I found that 72% -75% of the children were reported as having been exposed to some form of domestic or community violence at a young age (3.5– 6 years). Overall violence exposure, domestic victimisation and witnessing community violence by 4.5 years was associated with increased internalising and externalising behaviours at age 5. Polyvictimisation was associated with increased externalising behaviours. Associations between witnessing domestic violence (or community victimisation) exposure alone with mental health were less robust. Lastly, there were associations between lifetime exposure to violence by 4.5 years and poor selective attention, receptive language, nonverbal intelligence and inhibition at 5 years. This thesis highlights the adverse consequences of violence exposure in early life for mental health and cognitive problems in preschoolers living in high violence contexts. Mental health and cognitive problems manifest at an early age and emphasize the need for interventions to reduce violence exposure and its consequences in young children in LMICs.